Helplessness Beliefs and Social Withdrawal: The Mediating Role of Avoidant Coping - Rodrigues da Silva, Diana; Fernandes, Lucas (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to examine the mediating role of avoidant coping in the relationship between helplessness beliefs and social withdrawal among Brazilian young adults.Methods and Materials: A descriptive correlational design was employed with a sample of 418 participants aged 18–35 from Brazil, selected based on the Krejcie and Morgan sampling table. Standardized instruments were used to measure helplessness beliefs, avoidant coping, and social withdrawal. Data were analyzed using Pearson correlation via SPSS-27 to determine bivariate relationships and Structural Equation Modeling (SEM) via AMOS-21 to test the hypothesized mediation model. Assumptions of normality, linearity, and multicollinearity were assessed and confirmed prior to analysis.Findings: Results indicated significant positive correlations between helplessness beliefs and avoidant coping (r = .51, p < .001), helplessness beliefs and social withdrawal (r = .43, p < .001), and avoidant coping and social withdrawal (r = .48, p < .001). The SEM analysis demonstrated a good model fit (χ²/df = 2.05, CFI = .96, RMSEA = .049). Helplessness beliefs had a direct effect on avoidant coping (β = 0.51, p < .001) and social withdrawal (β = 0.26, p < .001). Avoidant coping had a significant direct effect on social withdrawal (β = 0.41, p < .001). The indirect effect of helplessness beliefs on social withdrawal via avoidant coping was also significant (β = 0.21, p < .001), confirming partial mediation. The total standardized effect from helplessness beliefs to social withdrawal was β = 0.47.Conclusion: The findings highlight avoidant coping as a significant behavioral mechanism linking helplessness beliefs to social withdrawal. Interventions aimed at restructuring cognitive appraisals and promoting adaptive coping strategies may be effective in reducing withdrawal-related behaviors in at-risk populations.